2016
DOI: 10.1038/srep36466
|View full text |Cite
|
Sign up to set email alerts
|

In vitro membrane protein synthesis inside Sec translocon-reconstituted cell-sized liposomes

Abstract: Protein synthesis using an in vitro transcription-translation system (IVTT) inside cell-sized liposomes has become a valuable tool to study the properties of biological systems under cell-mimicking conditions. However, previous liposome systems lacked the machinery for membrane protein translocation. Here, we reconstituted the translocon consisting of SecYEG from Escherichia coli inside cell-sized liposomes. The cell-sized liposomes also carry the reconstituted IVTT, thereby providing a cell-mimicking environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…These results indicated that the polyhistidine/nickel‐chelate affinity‐based membrane protein sorting system was an efficient preparation method of proteoliposomes integrated with not only α‐helix but also β‐barrel membrane proteins. Several studies demonstrated that translocon‐reconstituted proteoliposomes were useful for improved integration efficiency and orientation of IMPs under cell‐free membrane protein synthesis 11. Furthermore, membrane structure, such as surface charge and lipid composition, also affected the membrane protein topogenesis 20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the polyhistidine/nickel‐chelate affinity‐based membrane protein sorting system was an efficient preparation method of proteoliposomes integrated with not only α‐helix but also β‐barrel membrane proteins. Several studies demonstrated that translocon‐reconstituted proteoliposomes were useful for improved integration efficiency and orientation of IMPs under cell‐free membrane protein synthesis 11. Furthermore, membrane structure, such as surface charge and lipid composition, also affected the membrane protein topogenesis 20.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobic signal peptide or transmembrane domain of nascent proteins, generating from ribosomes, is recognized and protected by SRP and directed toward the endoplasmic reticulum membrane, resulting in safe sorting of the signal peptide or transmembrane domain of proteins into membranes 10. Several studies demonstrated that SecY/SecE/SecG translocon‐reconstituted proteoliposomes supplemented with other components, such as SRP, soluble SR, or SecA/B, enabled synthesis of IMPs in a cell‐free manner by facilitating their integration into and translocation across the liposomal membranes 11. Therefore, mimicking the SRP/SR–translocon pathway is a promising approach for improving the fate of membrane proteins in cell‐free membrane protein synthesis/liposome systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, after synthesis, the membrane proteins of interest are spontaneously inserted into the membranes of artificial cells, which normally yields a low ratio of membrane protein integration . To solve this problem, researchers try to mimic the translocation system in living cells, such as incorporating the Sec translocon inside cell‐sized liposomes along with the IVTT machinery of the targeted membrane protein, as was done by Ohta et al Interestingly, an active human mitochondrion‐derived calcium transporter, one of membrane proteins, has recently been reported to be successfully reconstituted in cell‐sized liposomes by using the IVTT system . For illustration, Figure B displays the synthesis and the localization of superfolder green fluorescent protein (sfGFP)‐labeled C‐X3‐C motif chemokine receptor 1 (CX 3 CR1), a G‐protein coupled receptor protein (GPCR), in GUVs by using a well‐known IVTT system named the protein synthesis using recombinant elements (PURE) system.…”
Section: A Bottom‐up Approach To Build An Artificial Cellmentioning
confidence: 99%
“…SecYEG has already been expressed with the PURE system on the outside and inside of vesicles and was shown to be functional as it translocated e.g. OmpA, YidC and EmrE into the membrane 238,239 . The studies supplemented the PURE system with either SecA and SecB or SRP and FtsY, which all help in bringing the membrane protein into the SecYEG channel (Fig.…”
Section: Current Progress Towards Synthetic Cellsmentioning
confidence: 99%
“…The studies supplemented the PURE system with either SecA and SecB or SRP and FtsY, which all help in bringing the membrane protein into the SecYEG channel (Fig. 3) [237][238][239] .…”
Section: Current Progress Towards Synthetic Cellsmentioning
confidence: 99%